The Influence of Price, Promotion, and Product Quality on Purchasing Decisions for Krampul Ice Tea in Sriwijaya, Semarang City (Case Study of Consumers of Krampul Ice Tea Drink Products in Sriwijaya, Semarang City) - Eriyanti, Novia; Nurhayati , Nurhayati (Economics and Business International Conference Proceeding, 2024)
The purpose of this research is to determine the influence of price, promotion, product quality and purchasing decisions. The population in this study were all consumers of kerampul iced tea throughout the city of Semarang. The sampling technique used in this research is a non-probability sampling technique. The sample used in this research used 100 respondents. The data analysis method in this research is quantitative analysis. The analysis technique in this research is quantitative descriptive analysis and multiple linear regression methods using SPSS version 22. The results of this research analysis show that price has a positive and significant effect on the decision to purchase krampul iced tea. Promotion has a positive and significant effect on purchasing decisions for krampul iced tea. Product quality has a positive and significant effect on purchasing decisions for krampul iced tea. Price, promotion and product quality simultaneously have a positive and significant effect on purchasing decisions for krampul iced tea.